Relationship Of Nutritional Status With Acute Respiratory Infection Incidence In Toddlers - Faradina Aghadiati (Universitas Pendidikan Indonesia, 2022)
ARI (Acute Respiratory Infection) in Indonesia always ranks first as the cause of infant mortality as much as 32.1% of infant mortality in 2009, and 38.8% cause of death in under-fives in 2011. ARI is also often on the list of the 10 most common diseases in hospitals. Based on data from the disease eradication (P2) ARI Program the coverage of ARI patients exceeded the target, the target set was only 16,534 cases but the results obtained were 18,749 (13,4%). This research is a descriptive analytic study with a case control approach. The research was carried out at the Jambi Health Center. The population in this study was the number of toddlers who were at the Jambi Public Health Center on July 2021, 1,110 toddlers. The sample in this study were 89 toddlers using the Accidental Sampling technique. Collecting data using medical records and questionnaire sheets as research aids. Data were analyzed by univariate and bivariate. The results of statistical tests using Chi-square show a p-value of 0.00 0.05, meaning that there is a significant relationship between nutritional status and the incidence of ARI in children under five at the Jambi Public Health Center in 2021. Efforts to reduce the incidence of ARI are expected in undernourished toddlers, as health workers must be more active in providing counseling to mothers who have toddlers about nutritious food needed by toddlers, it doesn't need to be expensive, the important thing is that the nutrients needed are fulfilled like Balanced Nutrition.